Revisiting The American (Youth) Dream in Matt Haig’s ‘The Midnight Library’ - Chrisna Aditya Siagian; Zuhrul Anam (Hasanuddin University, 2026)
This study examines the evolving representation of the American Dream in contemporary literature, emphasizing its relevance to youth perspectives in modern society. In The Midnight Library, the American Dream is portrayed as a shifting and negotiated concept, where younger generations move beyond traditional ideals of material success, social status, and externally defined achievements. The present study interprets Nora Seed’s actions as a representation of a negotiated version of the American Dream. The study aims to describe the behaviors and decisions that reflect the pursuit of the American Dream from a youth perspective, as well as to contextualize these actions as part of a broader redefinition of the concept itself. This research employs a descriptive qualitative approach, focusing on the analysis of non-numeric data derived from the narrative to generate interpretative insights. The findings reveal that contemporary youth redefine success by valuing small achievements, emotional and psychological well-being, and personal passions as meaningful sources of satisfaction, rather than adhering to traditional measures of success. In conclusion, The Midnight Library demonstrates that the concept of the American Dream has significantly evolved in contemporary society, reflecting changing values that emphasize individuality, authenticity, and inner fulfillment.